Simulation and optimization of the implantation of holmium atoms into metallic magnetic microcalorimeters for neutrino mass determination experiments - Gamer, Lisa; Enss, Christian; Fleischmann, Andreas; Gastaldo, Loredana; Velte, Clemens; Kempf, Sebastian (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2017)
Several novel experiments designed to investigate the electron neutrino mass in the sub-eV region are based on the calorimetric measurement of the 163Ho electron capture spectrum. For this the 163Ho source, with a required activity of the order of 1 to 100Bq, needs to be enclosed in the detector, having a volume smaller than 10−3mm3. Ion implantation is presently considered to be the most reliable method to enclose this source in the detector homogeneously distributed in a well defined volume. We have investigated the distribution of implanted holmium ions in different target materials and for different implantation energies by means of Monte Carlo simulations based on the SRIM software package. We show that, for a given implantation energy, a given target material and implantation area, the number of holmium ions that can be implanted in a single implantation run is limited. We discuss possible methods to overcome this saturation limit in order to fabricate detectors with an enclosed 163Ho source of the activity required by the experiments.
Gesehen am 26.03.2018